2017
DOI: 10.1002/2016jb013451
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and evolution of a fault‐controlled Quaternary basin by means of TDEM and single‐station ambient vibration surveys: The example of the 2009 L'Aquila earthquake area, central Italy

Abstract: We applied a joint survey approach integrating time domain electromagnetic soundings and single‐station ambient vibration surveys in the Middle Aterno Valley (MAV), an intermontane basin in central Italy and the locus of the 2009 L'Aquila earthquake. By imaging the buried interface between the infilling deposits and the top of the pre‐Quaternary bedrock, we reveal the 3‐D basin geometry and gain insights into the long‐term basin evolution. We reconstruct a complex subsurface architecture, characterized by thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 103 publications
1
30
0
Order By: Relevance
“…No direct measurements of V S are available within the PGC basin, so we describe the spatial change of f 0 as compared to top bedrock depth estimates from adjacent TDEM soundings in a qualitative way. Average V S values spanning ~500–900 m/s for the sedimentary infill of PGC are likely, as suggested by local geology, shallow borehole stratigraphy (see section 4) and also by ongoing studies in the same area and past works carried out in other similar basins of the central Apennines (Civico et al, ; Di Giulio et al, , ; MS–AQ Working Group, ).…”
Section: Methodsologymentioning
confidence: 78%
See 3 more Smart Citations
“…No direct measurements of V S are available within the PGC basin, so we describe the spatial change of f 0 as compared to top bedrock depth estimates from adjacent TDEM soundings in a qualitative way. Average V S values spanning ~500–900 m/s for the sedimentary infill of PGC are likely, as suggested by local geology, shallow borehole stratigraphy (see section 4) and also by ongoing studies in the same area and past works carried out in other similar basins of the central Apennines (Civico et al, ; Di Giulio et al, , ; MS–AQ Working Group, ).…”
Section: Methodsologymentioning
confidence: 78%
“…It is widely used to image the electrical properties of subsurface geological structures over different lithological settings with the capability to reach significant penetration depths over moderately resistive environments (few hundreds of meters; Bedrosian et al, ). We follow the approach by Civico et al () to map the top bedrock depths using 1‐D vertical resistivity models. We acquired 13 TDEM soundings both with central‐loop and offset receiver configurations using a 50‐m transmitter loop size along two transects (A‐A ' and B‐B′ in Figure ).…”
Section: Methodsologymentioning
confidence: 99%
See 2 more Smart Citations
“…Deng and Zhang () showed that active reverse faulting also generates colluvial wedges during a reverse faulting earthquakes and may also be used to identify reverse faulting earthquake events and in turn to analyze the paleo‐earthquake history. Shallow geophysical methods, in particular electrical resistivity studies, have become a successful practice in imaging fault zones, their attributes in a variety of geological settings, and image colluvial wedges/earthquake‐related structures (Buddensiek et al, ; Civico et al, ; Hanafy, ; Mattson, ; Maurya et al, ; Morey & Schuster, ; Ostrowski et al, ; Patidar et al, ; Pavan Kumar, Mahesh, et al, ; Sheley et al, ; Villani et al, ). In the present study, we carried out transient electromagnetic (TEM) investigations across the KMF zone (Figure ) to image the primary fault along with associated splays for better understanding the geometry of the fault zone.…”
Section: Introductionmentioning
confidence: 99%